Factors that Affect Ethical Behaviour on Accounting Students - Raymond Petrus Sugijaya; Aristanti Widyaningsih; Meta Arief (Universitas Pendidikan Indonesia, 2023)
This study aims at the factors that influence ethical perceptions in the ethical behavior on accounting students. This research method uses descriptive analytical research with a study of the literature that discusses the variables that influence student ethical behavior. The results of the literature study show that there are 18 factors that influence the ethical behavior of accounting students including level; performance; ethical easing; idealism level; professional code of ethics; intellectual intelligence; emotional intelligence; spiritual intelligence/religiosity; locus of control; love of money; gender; machiavallian; self-efficacy; conservation; relativism; and rationalization; ethical sensitivity; and ethical knowledge. Suggestions for further research are to explore other factors in other studies that are not reviewed in this study.